MODEL PENYELESAIAN CAROK BERDASARKAN CARA BERHUKUM ORANG MADURA - Budimansyah, Budimansyah (Faculty of Law, Tanjungpura University, 2018)
Carok is a social reality for the Madurese whose existence is still recognized today. The essence of Carok is more closely related to Madurese cultural values, where Carok is based on the fact that the Madurese have experienced the so-called